Impact of Covid-19 Pandemic on the Construction Industry in Malaysia: Issues and Challenges - Zainudin, Awang @ Omar (2024)
The COVID-19 pandemic in Malaysia has left a lasting impact on the construction industry with a suspensions and delays in projects progress and completion schedule that has created uncertainty at present and in the years ahead. It suffered a loss of approximately RM19 billion and also had to bear excess costs which also included more than 4,000 infections at various work sites as of December 2021 making it extremely vulnerable. While the pandemic may have brought with it some silver linings, it is crucial that the industry players to conduct research broadly and openly, lest future pandemic preparedness in research repeat the hard-fought lessons of today. The purpose of this research is to explore, explain and determine the factors that facilitate cause and effect of Covid 19 pandemic to the construction industry with a specific focus on the housing development’s issues and challenges. The study aims to provide a comprehensive analysis of the impact of the COVID-19 outbreak to contractors, developers and/or industrial players in Malaysia, society and the economy and to investigate the preventive measures taken to reduce the impact. Qualitative research approach using a single case study method was adopted for the data collection. The data was collected from multiple sources of evidence which comprised of semi-structured interviews, documentation review, observation and archival records. In-depth interviews were conducted with 50 individuals which comprise of founder, owner, director, shareholder, manager, engineer, consultant and worker of construction and housing development companies. This appropriate study design, collaboration, data collection and data sharing shall enable to unpacks the key responses to the issues and challenges, the efficacy of current initiatives, and summarize the lessons learnt as an update on the information available to the industry, business, authorities and societies. In addition, this research is to develop and evaluate innovative strategies and technologies to improve access to the project management, quality, safety, and cost effectiveness in the construction industry. This report review captures a number of specific suggestions for support. For example, support for the industry players, government, societies, key management and workers, creating safer construction site’s environments, wide-scale financial support, greater awareness around the industry which were badly affected by COVID-19 and putting in place robust processes for learning and reflection on the impact of the pandemic. This report will benefit construction firms, governments, leaders, and customers in addressing a pandemic-like situation in the future.